2022
DOI: 10.3389/fneur.2021.736704
|View full text |Cite
|
Sign up to set email alerts
|

One PMP22/MPZ and Three MFN2/GDAP1 Concomitant Variants Occurred in a Cohort of 189 Chinese Charcot-Marie-Tooth Families

Abstract: Background and AimsCharcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous group of inherited peripheral neuropathies. The wide phenotypic variability may not be completely explained by a single mutation.Aims and MethodsTo explore the existence of concomitant variants in CMT, we enrolled 189 patients and performed molecular diagnosis by application of next-generation sequencing combined with multiplex ligation-dependent probe amplification. We conducted a retrospective analysis of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(37 reference statements)
0
1
0
1
Order By: Relevance
“…3 Studies have revealed that AD-inherited mutant forms of GDAP1 gain an abnormal function that impairs mitochondrial fusion, increases reactive oxygen species production, and initiates apoptosis, 23 Based on the available clinical data, the majority of GDAP1- in families with the R120W mutation 13 and the association of concomitant variants in GDAP1 and MFN2 with a more severe phenotype. 25 Therefore, these possibilities should be considered when significant clinical heterogeneity is observed, emphasizing the importance of comprehensive genetic counseling associated with genetic testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Studies have revealed that AD-inherited mutant forms of GDAP1 gain an abnormal function that impairs mitochondrial fusion, increases reactive oxygen species production, and initiates apoptosis, 23 Based on the available clinical data, the majority of GDAP1- in families with the R120W mutation 13 and the association of concomitant variants in GDAP1 and MFN2 with a more severe phenotype. 25 Therefore, these possibilities should be considered when significant clinical heterogeneity is observed, emphasizing the importance of comprehensive genetic counseling associated with genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the co‐existence of Q38R in the proband of Family 15 resulted in a more pronounced and severe phenotypic effect than the dominant variant V219G inherited from her family. Previous studies have also reported significant phenotypic variability in GDAP1 ‐related CMT such as reduced penetrance in families with the R120W mutation 13 and the association of concomitant variants in GDAP1 and MFN2 with a more severe phenotype 25 . Therefore, these possibilities should be considered when significant clinical heterogeneity is observed, emphasizing the importance of comprehensive genetic counseling associated with genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the cumulative effect of GDAP1 and MFN2 gene sequence variants was established. [ 19 , 20 , 21 , 22 ]. Such a genetic interaction is observed when proteins encoded by mutated genes participate in the same process.…”
Section: Discussionmentioning
confidence: 99%
“…Il existe parfois des situations complexes ou plusieurs gènes peuvent être impliqués chez une même personne atteinte de CMT (13,14). Il est également possible qu'un fragment de chromosome soit dupliqué ou au contraire supprimé, pouvant entraîner des variations du nombre de copies des gènes présents sur ce fragment.…”
Section: C) Mode De Transmissionunclassified